Manajemen Kurikulum Fungsional Dalam Meningkatkan Kemandirian Peserta Didik Berkebutuhan Khusus di SLB-A Bartemeus Manado - Kiriweno, Henny B. A; Sumual, Tineke Evie Meggy; Dapa, Aldjon Nixon (Peneliti.net, 2023)
The aim of this research is to describe functional curriculum management in increasing the independence of Students with Special Needs at SLB-A Bartemeus Manado. Basically, every child needs to be taught independence. Teaching independence to students with special needs requires greater effort than to children without disabilities. It became interesting when initial observations were made at SLB-A Bartemeus Manado, a school that focuses on students with special needs, with visual impairments. The education provided is different from schools in general. This school uses a functional curriculum where the focus of this curriculum is increasing independence from life skills. This study uses a qualitative method. Data collection techniques are carried out by observation, interviews and documentation. Data analysis was carried out descriptively, qualitatively and interpretively. The research results show that through good planning, organization, implementation and evaluation, functional curriculum management at SLB A Bartemeus Manado can ensure that students with disabilities receive education that suits their needs and potential. The impact of implementing a functional curriculum is that students are able to experience independence in their daily activities, without being completely dependent on other people. The functional curriculum is able to provide activities that can train students to continue their activities without significant obstacles or having to wait for intervention from other people.